Genome-wide multi-omics profiling of colorectal cancer identifies immune determinants strongly associated with relapse - Madhavan, Subha; Gusev, Yuriy; Natarajan, Thanemozhi G.; Song, Lei; Bhuvaneshwar, Krithika; Gauba, Robinder; Pandey, Abhishek; Haddad, Bassem R.; Goerlitz, David; Cheema, Amrita K.; Juhl, Hartmut; Kallakury, Bhaskar; et al. (Frontiers in Genetics, 2013)
The use and benefit of adjuvant chemotherapy to treat state II colorectal cancer (CRC) patients is not well understood since the majority of these patients are cured by surgery alone. Identification of biological markers of relapse is a critical challenge to effectively target treatments to the ~20% of patients destined to relapse. We have integrated molecular profiling results of several ‘omics’ data types to determine the most reliable prognostic biomarkers for relapse in CRC, using data from 40 stage I and II CRC patients. We identified 31 multi-omics features that highly correlate with relapse. The data types were integrated using multi-step analytical approach with consecutive elimination of redundant molecular features. For each data type a systems biology analysis was performed to identify pathways, biological processes and disease categories most affected in relapse. The biomarkers detected in tumors, urine and blood of patients indicated a strong association of immune processes, including aberrant regulation of T-cell and B-cell activation that could lead to overall differences in lymphocyte recruitment for tumor infiltration and markers indicating likelihood of future relapse. The immune response was the biologically most coherent signature that emerged from our analyses among several other biological processes, and corroborates other studies showing a strong immune response in patients less likely to relapse.